2017
DOI: 10.1016/j.neo.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HPV E6/E7 siRNA with Chemotherapeutic Agents on the Regulation of TP53/E2F Dynamic Behavior for Cell Fate Decisions

Abstract: Toxicity and resistance remain major challenges for advanced or recurrent cervical cancer therapies, as treatment requires high doses of chemotherapeutic agents. Restoration of TP53 and hypophosphorylated-retinoblastoma (pRB) proteins by human papillomavirus (HPV) E6/E7 siRNA sensitizes HPV-positive cervical cancer cells toward chemotherapeutic agents. Here, we investigated the therapeutic effects of E6/E7 siRNA on the dynamic behavior of TP53 and RB/E2F signaling networks in deciding the cell fate. The synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
3
3
0
Order By: Relevance
“…Another study also reported suppressed cell growth in HPV-related cervical cancer cells after downregulating HPV 16 E6 and E7 using an adenovirus-mediated transfection which correlated with higher expression of p53 and/or pRb proteins 50 , 51 . Additionally, a similar effect of increased sensitization to cisplatin treatment has been shown in cervical cancer cells after treatment with siRNA against the HPV 16 and HPV 18 E6 and E7 52 . Furthermore, downregulation of HPV 16 and HPV 18 E6 and E7 led to radiosensitizing effects and suppressed growth in cervical cancer cells and xenograft mouse tumors 53 .…”
Section: Current Screening and Treatment Strategies For Hpv-associatesupporting
confidence: 59%
“…Another study also reported suppressed cell growth in HPV-related cervical cancer cells after downregulating HPV 16 E6 and E7 using an adenovirus-mediated transfection which correlated with higher expression of p53 and/or pRb proteins 50 , 51 . Additionally, a similar effect of increased sensitization to cisplatin treatment has been shown in cervical cancer cells after treatment with siRNA against the HPV 16 and HPV 18 E6 and E7 52 . Furthermore, downregulation of HPV 16 and HPV 18 E6 and E7 led to radiosensitizing effects and suppressed growth in cervical cancer cells and xenograft mouse tumors 53 .…”
Section: Current Screening and Treatment Strategies For Hpv-associatesupporting
confidence: 59%
“…Furthermore, HPV 16, 18 E6/E7 siRNA significantly inhibits invasion of CC cells (Figures 7J,K). We also confirmed the p53 restoration and Rb expression level in our previous studies by using the HPV 16/18 E6-E7 siRNA (39, 41). We hypothesized that HPV 16 and 18 E6-E7 viral oncogenes could induce differential miR-375 expression which contributed to the cervical tumorigenesis.…”
Section: Resultssupporting
confidence: 88%
“…For siRNA transfection, AEG-1 siRNA 1 (referred as AEG-1 siRNA) (sense: 5′-GACACUGGAGAUGCUAAUAUU-3′, antisense: 5′-UAUUAGCAUCUCCAGUGUCUU-3′), AEG-1 siRNA 2 (sense: 5′-GGUGAAGAUAACUCUACUGUU-3′, antisense: 5′-CAGUAGAGUUAUCUUCACCUU-3′) and their negative control siRNA (SIC008) were synthesized and purchased from sigma aldrich, USA. A pool of three different siRNA for HPV 16 E6/E7 and HPV 18 E6/E7 (kindly gifted from Prof. Young Kee Shin, Research Institute of Pharmaceutical Science, Seoul National University, Seoul, Republic of Korea) (39), and for miRNA transfection, miR-375 mimic (HMI0537), miR-mimic-negative control (HMC0002), miR-375 inhibitor (HSTUD0537), and miR-inhibitor-negative control (NCSTUD001) (Sigma Aldrich, USA) were transiently transfected into cells at a concentration of 20 nM using Lipofectamine RNAiMAX Reagent (Invitrogen). The mock control cells were treated with transfection reagent alone and the cells were maintained for 48 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that p53 overexpression may restore RB expression through some pathways. Previous reports have confirmed the cross-talk between p53 and Rb/E2F signaling mechanisms (Rajasekaran et al, 2017). We can see that E7 is still expressed in the basal region.…”
Section: Discussionsupporting
confidence: 82%